2005
DOI: 10.1104/pp.105.062372
|View full text |Cite
|
Sign up to set email alerts
|

NpPDR1, a Pleiotropic Drug Resistance-Type ATP-Binding Cassette Transporter from Nicotiana plumbaginifolia, Plays a Major Role in Plant Pathogen Defense

Abstract: Nicotiana plumbaginifolia NpPDR1, a plasma membrane pleiotropic drug resistance-type ATP-binding cassette transporter formerly named NpABC1, has been suggested to transport the diterpene sclareol, an antifungal compound. However, direct evidence for a role of pleiotropic drug resistance transporters in the plant defense is still lacking. In situ immunolocalization and histochemical analysis using the gusA reporter gene showed that NpPDR1 was constitutively expressed in the whole root, in the leaf glandular tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
163
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 68 publications
16
163
1
Order By: Relevance
“…Alternatively, this gene could be a novel marker for the stress experienced by pen3 plants. In spite of the expression responses, loss of PDR12 function in Arabidopsis or PDR1 function in N. plumbaginifolia did not lead to increased susceptibility to several fungal and bacterial pathogens (Campbell et al, 2003;Stukkens et al, 2005). However, N. plumbaginifolia plants lacking PDR1 were highly susceptible to the necrotroph B. cinerea (Stukkens et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Alternatively, this gene could be a novel marker for the stress experienced by pen3 plants. In spite of the expression responses, loss of PDR12 function in Arabidopsis or PDR1 function in N. plumbaginifolia did not lead to increased susceptibility to several fungal and bacterial pathogens (Campbell et al, 2003;Stukkens et al, 2005). However, N. plumbaginifolia plants lacking PDR1 were highly susceptible to the necrotroph B. cinerea (Stukkens et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In spite of the expression responses, loss of PDR12 function in Arabidopsis or PDR1 function in N. plumbaginifolia did not lead to increased susceptibility to several fungal and bacterial pathogens (Campbell et al, 2003;Stukkens et al, 2005). However, N. plumbaginifolia plants lacking PDR1 were highly susceptible to the necrotroph B. cinerea (Stukkens et al, 2005). With this result and the cloning of PEN3, PDR-type ABC transporters have been implicated in defense, adding a new role to the diverse repertoire of the PDR-like ABC transporter family.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, only a few in vivo substrates have been identified, such as cadmium and auxin for ABCG36 (PDR8), 2,4-dichlorophenoxy acetic acid for ABCG37 (PDR9), and abscisic acid for ABCG40 (PDR12; Kim et al, 2007;Strader and Bartel, 2009;Kang et al, 2010). However, there is some evidence that plant PDRs may transport a variety of secondary metabolites, including antimicrobial and antifungal compounds, as well as xenobiotics and heavy metals (Martinoia et al, 2002;Campbell et al, 2003;Moons, 2003;Ducos et al, 2005;Stukkens et al, 2005;Ito and Gray, 2006;Kobae et al, 2006;Stein et al, 2006;Krattinger et al, 2009).…”
Section: Pec1 Is the Pdr-type Transporter Abcg32mentioning
confidence: 99%
“…There is also increasing evidence for the involvement of ABC transporters in defence. Stukkens et al (2005) found that a PDR protein in tobacco leaves (NpPDR1) was induced following pathogen attack and silencing of NpPDR1 by RNA interference resulted in increased sensitivity to the plant pathogen Botrytis cinerea. More recently Kobae et al (2006) demonstrated that a loss of an Arabidopsis plasma membrane-localized PDR ABC transporter (AtPDR8) lead to hypersensitive cell death upon pathogen infection.…”
Section: Defence-related Genesmentioning
confidence: 99%